Eficiência da imunoterapia no tratamento do linfoma de células b em cães - Sato, Bruna Yukie Nakaguma [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Lymphoma is the most spontaneously occurring tumor in dogs and the B-cell lymphoma is the most common form. The goal of immunotherapy is to initiate or re-initiate immune responses against cancer cells by avoiding tumor amplification and propagation. This systematic review aimed to evaluate the efficiency of immunotherapy for the treatment of B-cell lymphoma in dogs. METHODS: PUBMED, and Science Direct databases were accessed through Capes Periodics during March to May of 2017 and the strategy used was immunotherapy OR vaccine AND B-cell AND lymphoma AND canine. Only experimental trials published in the last ten years, in English and related to immunotherapeutic methods, isolated or associated with another form of treatment were included. RESULTS: The search resulted in 867 articles and after the application of the inclusion and exclusion criteria, 8 studies were selected, 87.5% was about vaccine as a form of immunotherapy, 25% was randomized and double-blinded. CONCLUSION: There are varieties of immunotherapies that stimulate the immune system, causing antitumor effect, improving the time of survival, better tumor remission time and not causing serious side effects. Therefore, those should be evaluate with larger studies, randomized and with a larger number of dogs, in order to verify their efficiency and drug interaction when associated to several chemotherapy protocols performed prior, concomitant and after immunotherapy

O linfoma é o tumor de maior ocorrência espontânea em cães, sendo o de células B a forma mais comum. O objetivo da imunoterapia é iniciar ou reiniciar as respostas do sistema imune contra as células cancerígenas evitando a amplificação e a propagação tumoral. Esta revisão sistemática teve como objetivo avaliar a eficiência da imunoterapia para o tratamento de linfoma de células B em cães. MÉTODO: foram consultados as bases de dados PUBMED, e Science Direct com acesso através do Capes Periódicos durante março a maio de 2017 e a estratégia utilizada foi "immunotherapy" OR "vaccine" AND "B-cell" AND "lymphoma" AND "canine". Foram incluídos apenas ensaios experimentais com data de publicação nos últimos dez anos, idioma inglês e relacionados a métodos imunoterápicos, isolados ou associados com outra forma de tratamento. RESULTADOS: a busca resultou em 867 artigos e após a aplicação dos critérios de inclusão e exclusão foram selecionados 8 trabalhos, sendo que 87,5% abordaram a vacina como método de realização da imunoterapia, 25% eram randomizados e duplo-cego. CONCLUSÃO: há uma variedade de imunoterapias que estimulam o sistema imune, causando efeito antitumoral, melhorando a sobrevivência e o tempo de remissão do tumor sem gerar efeitos colaterais graves. Portanto, estas deveriam ser avaliadas com maiores estudos, randomizados e com maior número de cães, a fim de verificar sua eficiência e interação medicamentosa quando associadas a diversos protocolos quimioterápicos realizados prévia, concomitante e posteriormente à imunoterapia
Keywords: Vacinas; Imunoterapia; Cancer; Linfoma; Cães; vaccine